Research on OSNR and BER of 40G DWDM system on DRZ - FENG Xiancheng; LI Xiaopeng; SI Qinghua (Institute of Advanced Engineering and Science, 2013)
The signal modulation format is a key issue for 40 G DWDM fiber optical communication system , which determines transmission quality and spectral efficiency. Firstly, 他he scheme of key technologies and modulation format (ODB, CSRZ, DRZ, DPSK, DQPSK) of 40G DWDM system is introduced. Through the Q value with OSNR and BER, the theoretical curve between OSNR and BER is given. And then it proposes optical interface parameters requirements of 40G DWDM system. By way of adopting VOA compensation in experimental system,OTU typical spectrum,eye diagram,BER and OSNR performances have been tested and analyzed. Experiment results show that DRZ code have better transmission performance, are suitable for long or middle distance transmission, meet the demand of commercial application. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.2058